Detecting genetic modifiers of spondyloepimetaphyseal dysplasia with joint laxity in the Caucasian Afrikaner community. (25th October 2018) - Chimusa, Emile R; Beighton, Peter; Kumuthini, Judit; Ramesar, Rajkumar S
Abstract: Spondyloepimetaphyseal dysplasia with joint laxity (SEMDJL) is an autosomal-recessive skeletal dysplasia. A relatively large number of patients with SEMDJL have been identified in the Caucasian Afrikaans-speaking community in South Africa. We used a combination of Genome-Wide Human Single Nucleotide Polymorphism (SNP) Array 6.0 data and whole exomic data to potentially dissect genetic modifiers associated with SEMDJL in Caucasian Afrikaans-speaking patients. Leveraging the family-based association signal in prioritizing candidate mutations, we identified two potential modifier genes, COL1A2 and MATN1, and replicating previously identified mutation in KIF22 . Importantly, our findings of genetic modifier genes and previously identified mutations are layered on the same sub-network implicated in syndromes characterized by skeletal abnormalities and intellectual disability, bone and connective tissue fragility. This study has potentially provided crucial insights in identifying the indirect modifying mutation(s) linked to the true causal mutation associated with SEMDJL. It is a critical lesson that one may use constructively especially when the pace of exomic sequencing of rare disorders continues apace.